Ethnobotany of Tharu community of Pakali, Sunsari, Nepal - Chaudhary, Shravan Kumar; Rai, Shiva Kumar (Nepalese Journal of Biosciences, 2017)
Ethnobotany of Tharu community of Pakali, Sunsari has been studied. The study identified a total 119 plants under 92 genera and 52 families using by them for different purposes such as traditional medicinal practices (92.4% plants), cultural and religious ceremonies (27.7% plants), edible (37.8% plants), fodder (17.6% plants) etc. The community is using large number of plants for the treatment of more than 60 human diseases. Maximum plants (17.74) are used for stomach problem and then expelling worm, skin disease, diarrhea, dysentery and cough, rheumatism, fever and eye problems. There are few but important plants which are effective in abortion, gonorrhea, dyspepsia, appetizer, eczema, tumour, head ache, chest pain, cancer, kidney problem, cholera etc. It has been clear that the Tharu of Pakali have a good knowledge of medicinal plants and their uses.